Rancangan Prototype Alat Jemuran Otomatis Menggunakan Sensor Air Dan Sensor Cahaya Berbasis Mikrokontroller Arduino - Irwanto Irwanto; Endi Permata; Didik Aribowo (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
The development of science and technology has experienced rapid development, so as to encourage people to try to overcome all the problems that arise around them and ease the work that is around the environment. One of the technologies developed at the moment is the Arduino microcontroller. Design of Automatic Clothesline Using Water Sensor and Light Sensor, Based on Arduino Microcontroller. Based on the problems that are often experienced by boarding children or families when leaving clothesline at home. Rain or bad weather until now has become a major problem for people who have clothesline, so clothes that are already dry become wet with rain water when the occupants of the house are outside the house. To overcome these problems, the authors designed an automatic clothesline using water sensors and light sensors based on Arduino microcontrollers. The author uses the Atmega16 microcontroller as the automatic clothesline roof control center. The sensors needed in the automatic clothesline controller are light sensors and water sensors. For light sensors used LDR (Light Diode Resistors) and electrode sensors as rainwater sensors. LDR is a type of resistor whose resistance value is influenced by light. Electrode sensor is a sensor that utilizes the conductance properties of a material. The servo motor of the prototype system can move shut and clothesline from an angle of 0 to an angle of 90 when the water sensor and light sensor detect changes in the weather around the environment and the tool design system is in accordance with the design that has been made.